PENINGKATAN KOMPETENSI SISWA PADA MATERI TATA SURYA MELALUI MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN IPA KELAS IX SMPN 2 CANDUNG - Netti, Ftira (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The research is classroom action research by applying the model of Discovery Learning, which aims to improve the competence of students on the Solar System lesson in natural science learning in ninth grade. This study was conducted in two cycles. Each cycle consists of three face to face.  Each four sessions consists of planning, action, observation and test. Based on data analysis is seen an increase in the competence affective, psychomotor and cognitive of student from the first cycle to the second cycle. Based on the results of this research is concluded that there was an in-crease in student learning outcomes. So it can be ascertained that the Discovery Learning model is appropriate to be implemented in order to improve the competence of students.